Reducing social diabetes distress with a conversational agent support system: a three-week technology feasibility evaluation - Bruijnes, Merijn; Kesteloo, Mitchell; Brinkman, Willem-Paul (Frontiers in Digital Health, 2023)
People with diabetes mellitus not only have to deal with physical health problems, but also with the psycho-social challenges their chronic disease brings. Currently, technological tools that support the psycho-social context of a patient have received little attention. The objective of this work is to determine the feasibility and preliminary efficacy of an automated conversational agent to deliver, to people with diabetes, personalised psycho-education on dealing with (psycho-)social distress related to their chronic illness. In a double-blinded between-subject study, 156 crowd-workers with diabetes received a social help program intervention in three sessions spaced over three weeks. They were randomly assigned to receive support from either an interactive conversational support agent (n=79) or a self-help text from the book ``Diabetes burnout'' as a control condition (n=77). Participants completed the Diabetes Distress Scale (DDS) before and after the intervention, and after the intervention the Client Satisfaction Questionnaire (CSQ-8), Feeling of Being Heard (FBH), and System Usability Scale (SUS). Results indicate that people using the conversational agent have a larger reduction in diabetes distress (M = -0.305, SD = 0.865) than the control group (M = 0.002, SD = 0.743) and this difference is statistically significant (t(154) = 2.377, p = 0.019). A hypothesised mediation effect of `attitude to the social help program' was not observed. An automated conversational agent can deliver personalised psycho-education on dealing with (psycho-)social distress to people with diabetes and reduce diabetes distress even more than a self-help book. This study has been preregistered with the Open Science Foundation under [blinded for review], and has been accepted by the Human Research Ethics Committee of the [blinded for review].